Plutonic Development of the Ilordleq Area, South Greenland. Part II: Late-Kinematic Basic Dykes. - Watterson, Juan (Meddelelser om Grønland, 1968)
Basic dykes with primary amphibolite facies mineral assemblages were emplaced along active transcurrent fissures in the closing stages of a period of plutonic activity. The order of crystallisation, determined from petrographic evidence and from the composition of filter-pressed fractions, is consistent with consolidation of the magma at ca. 4000 bars water pressure at 800- 850°C. The marked calc-alkaline trend of differentiation and the high-alumina characteristics of some dykes, illustrated by ten chemical analyses, is shown to be the likely result of a fractionation dominated by the separation of mafic from felsic phases. This type of fractionation is shown to be a consequence of the conditions under which the dykes crystallised, and is contrasted with fractionation taking place under conditions of low water pressure. The type of differentiation demonstrated by the dyke suite is shown to be capable of producing many of the characteristic features of the orogenic volcanic suite, including relatively large amounts of intermediate differentiates. Oblique foliation in the dykes is shown to be related to transcurrent movements and is interpreted by reference to a model of rotational homogenous strain.